Production and characterization of porous titanium applied in biomaterial - Bomfim, Pâmela K. S. (2017)
The development of materials with a porous titanium surface has been widely studied in the field of biomaterials due to the excellent biocompatibility, high corrosion resistance and combination of high strength with low density. Another relevant fact is that porosity allows bone tissue growth. However, the high reactivity in liquid state ends up hindering titanium fusion, so an alternative is the powder metallurgy (PM).The aim of this work was to produce porous titanium samples by conventional PM. Porous samples was characterized by porosity and microstructure (optical microscopy - OP and scanning electron microscopy SEM), crystaline phase (X-ray diffraction –XRD), mechanical properties (three point bending test) and cytotoxic test. The results showed the presence of alpha phase, a decrease in the elasticity modulus, increase in average pore size and samples exhibited no toxic effects.